Academic digital library in Malaysia: A case study on the status of digital reference services - Wan Dollah, Wan Ab. Kadir; Abdul Kadir, Razilan (2010)
This paper highlights the current status of digital library services provided by selected public academic libraries in Malaysia. The drift from traditional library to digital library architecture has set drastic changes in favor of adopting knowledge-gain mechanisms via the use of networked and digital environments. With diversity of functions, academic digital library is seen the most awaiting proxy in changing the information culture among academic users. This paper in general attempts to highlight the phenomena of using digital library system in public universities in Malaysia. The focal of the discussion is on digital reference services of academic digital library.